2018
DOI: 10.1016/j.jaci.2017.12.491
|View full text |Cite
|
Sign up to set email alerts
|

Human Factors Engineering Validation Study for a Novel 0.1 mg Epinephrine Auto-Injector

Abstract: RATIONALE: Anaphylaxis in infants and young children is increasing. Currently available epinephrine auto-injectors (EAIs) are not FDA approved for patients weighing <15 kg, and therefore, EAIs are prescribed off-label for these patients. Ultrasound studies suggest currently marketed 0.15 mg EAIs have needle lengths that may strike bone in ;29-43% of patients weighing <15 kg, resulting in possible intraosseous injection. An EAI with a shorter needle length has been developed to help potentially minimize the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…20 Additional human factors engineering studies for Auvi-Q have demonstrated device labeling features and voice prompts were effective in communicating proper use, although training and/or patient information leaflets/ instructions for use were also provided. 21,22 Labeling information for US Food and Drug Administrationeapproved devices note that individuals should be trained on and familiar with EAI use. 32,33 Yet, proper EAI administration technique is often lacking in patients, caregivers, and health care practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…20 Additional human factors engineering studies for Auvi-Q have demonstrated device labeling features and voice prompts were effective in communicating proper use, although training and/or patient information leaflets/ instructions for use were also provided. 21,22 Labeling information for US Food and Drug Administrationeapproved devices note that individuals should be trained on and familiar with EAI use. 32,33 Yet, proper EAI administration technique is often lacking in patients, caregivers, and health care practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…The next topic addressed in this Proceedings deals with the use of epinephrine for the management of severe allergic reactions that manifest as anaphylaxis, whether induced by drugs, foods, or other agents. In this issue, Edwards et al 20 present the results of a human factors engineering study which validated the user interface for a novel 0.1-mg epinephrine autoinjector. This is a welcome therapeutic option as it addresses an unmet need in anaphylaxis management for infants who weigh under 33lbs (15kg).…”
mentioning
confidence: 99%